2014
DOI: 10.1155/2014/836157
|View full text |Cite
|
Sign up to set email alerts
|

A Higher Frequency of CD4+CXCR5+T Follicular Helper Cells in Adult Patients with Minimal Change Disease

Abstract: Background. T follicular helper (TFH) cells are involved in the humoral immune responses. This study is aimed at examining the frequencies of different subsets of CD4+CXCR5+ TFH cells in adult patients with minimal change disease (MCD). Methods. A total of 27 patients and 14 healthy controls (HC) were characterized for the levels of sera cytokines, inducible T-cell costimulator (ICOS), and programmed death 1 (PD-1) of positive TFH cells by flow cytometry. The level of sera IL-21 was examined; 24 h urinary prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The serum levels of interleukin-17A, interferon-g, interleukin-2, interleukin-10, interleukin-4, and interleukin-21 are significantly higher in patients with MCD than in healthy controls, and this may translate into foot process fusion and consequent nephrotic syn-haematologica | 2015; 100 (9) © F e r r a t a S t o r t i F o u n d a t i o n drome. 41,42 A similar mechanism has been advocated for MCD complicating B-cell neoplasias, including CLL and other non-Hodgkin lymphomas, in which T-cell dysfunction is a common finding. 23,43,44 It should be noted that all cases of MCD in our series presented with the nephrotic syndrome.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 98%
See 1 more Smart Citation
“…The serum levels of interleukin-17A, interferon-g, interleukin-2, interleukin-10, interleukin-4, and interleukin-21 are significantly higher in patients with MCD than in healthy controls, and this may translate into foot process fusion and consequent nephrotic syn-haematologica | 2015; 100 (9) © F e r r a t a S t o r t i F o u n d a t i o n drome. 41,42 A similar mechanism has been advocated for MCD complicating B-cell neoplasias, including CLL and other non-Hodgkin lymphomas, in which T-cell dysfunction is a common finding. 23,43,44 It should be noted that all cases of MCD in our series presented with the nephrotic syndrome.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 98%
“…41,42 A similar mechanism has been advocated for MCD complicating B-cell neoplasias, including CLL and other non-Hodgkin lymphomas, in which T-cell dysfunction is a common finding. 23,43,44 It should be noted that all cases of MCD in our series presented with the nephrotic syndrome.…”
mentioning
confidence: 98%
“…Data from human studies on cTfh cells in RA patients clearly corroborate mouse data on aberrant Tfh numbers ( Table 1 ). Several studies have reported an increase in cTfh cells in RA patients, accompanied by elevated IL-21 levels in some cases [ 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. However, it is important to note that while there are increase Tfh numbers both in murine and human GCs, the underlying mechanism responsible for their expansion remains to be fully unraveled.…”
Section: Germinal Centers In Rheumatoid Arthritismentioning
confidence: 99%
“…Arroyo-Villa et al [65] RA patients with active disease have a higher frequency of Tfh cells and a higher Tfh/Tfr ratio resulting from lower Tfr frequencies Zhang et al [66] Increased frequencies of Tfh cells and IL-21 in RA patients which correlates positively with DAS28 Wang et al [67], Zhou et al [69] Increased frequencies of Tfh cells in newly diagnosed RA patients correlating with activated B cells and DAS28 Niu et al [68] Elevated frequencies of Tfh cells, IL-21 and PD-1 in RA patients with active disease Nakayamada et al [70] Higher proportions of Tfh cells in RA patients with active disease and, treatment with Abatacept reduces Tfh cell levels. Su et al [71] Elevated frequencies of Tfh cells in RA patients compared to HCs…”
Section: Tfh Cells In Ra Findingsmentioning
confidence: 99%
“…Moreover, they also suppress intestinal inflammation in murine models [ 23 , 24 ]. In previous studies, we have proved that activated B and T follicular helper (TFH) cells can contribute to the pathogenesis of minimal change disease (MCD) and hepatitis B virus-associated membranous nephropathy (HBV-MN) [ 25 , 26 ]. In addition, we have found that several CD19 + B cell subtypes and IL-10 + Bregs are differentially expressed in IgA-nephritis patients [ 27 ].…”
Section: Introductionmentioning
confidence: 99%